Storm Riders - Weis, Margaret; Krammes, Robert (New York : Tor, 2013)
"In a world where magic is intrinsic to the fabric of everyday life, two kingdoms, centuries-long enemies, have long sought a powerful magical weapon that will win them lasting dominance. But neither realm is ready when they are both attacked by the Bottom-Dwellers, a bitter people whose own land was destroyed, and who now live only to take vengeance on those they blame for a wretched life in the storm-tossed abyss they inhabit"--
Keywords: Magic -- Fiction; Imaginary wars and battles -- Fiction; FICTION / Fantasy / General; Fantasy fiction